An Assessment of Anti-hyperglycemic Drug Utilization Patterns and Adherence to AACE/ACE 2015 Guidelines in South Indian Tertiary Care Teaching Hospital - Nuthakki, Siddhartha; Pendyala, Sivaprasad; Vallabhu, Charan; Kilaru, Naveenbabu; Challa, Siva R; Pingili, Ravindrababu (Indian Journal of Pharmacy Practice)
Aim: To compare adherence to American Association of Clinical Endocrinologists/American College of Endocrinology (AACE/ACE) 2015 guidelines for diabetes care in a tertiary care teaching hospital in India. Method: In this prospective observational study, 415 prescriptions of type 2 diabetes mellitus (T2DM) patients were collected in Dr. Pinnamaneni Siddhartha Institute of Medical Sciences (PSIMS) hospital from January 2015 and June 2015. Medication adherence to AACE/ACE guidelines was assessed based on glycated haemoglobin (HbA1C) values. Results: A total of 201 (48.4%) male and 214 (51.6%) female patients were identified. The mean age was 53.57 ± 10.77 years (male) and 53.69 ± 10.71 years (females). Patients with HbA1C <7.5% (37.3%, male; 45.3%, female) were predominant followed by HbA1C 7.5% - 9% (32.3%, male; 35.3%, female) and HbA1C > 9.0% (30.4%, male; 19.2%, female). Hypertension (HTN) (39.8%, male; 39.7%, female) is the most predominant co-morbidity, followed by patients with both HTN and cardio vascular diseases (CVDs) (9.4%, male; 9.8%, female). Insulin was prescribed to control hyperglycaemia in most of the cases (40.0%) followed by dual therapy (26.9%) and triple therapy (17.8%). The overall adherence rate was 88.3% for patients with HbA1C <7.5% (P< 0.0001); 98.7% for patients with HbA1C 7.5%-9%(P<0.0001)and 100% for patients with HbA1C >9%(P<0.0001). Conclusion: Optimal medication adherence is the ultimate goal to control the hyperglycemia in DM. The present study results revealed that the anti-diabetic medication adherence to AACE/ACE 2015 guidelines were optimal by the prescribers.
Keywords: Type 2 Diabetes Mellitus; Medication adherence; HbA1C; AACE/ACE guidelines; Antihyperglycemicdrugs; Physician prescribing pattern